A study on the factors that influence real estate investment trust (REITs) in Malaysia / Fateihah Abdul Wahab - Abdul Wahab, Fateihah (2014)
This study focused on the factors that influence the Real Estate Investment Trust (REITs) in Malaysia. The researcher applied the multiple linear regressions in modeling the factors influence REITs. There are three factors which is interest rate, exchange rate and inflation rate have been analyzed using monthly basis data from year 2006 until 2012. The researcher found that multiple linear regressions gave the R2 value of 0.628, meaning 62.8% of variance in REITS could be explained by interest rate, exchange rate and inflation rate. While, the t-test showed that the parameter estimates is significant at five percent level. Both independent variables that is exchange rate and inflation rate have a significant relationship with REITs. The values of both variables are 0.000. On the other hand, interest rate does not have significant relationship with REITs. It can be prove by the value of t-test that is 0.314. From the f-test, overall model can be accepted because of have a significant value between independent variables (interest rate, exchange rate and inflation rate) and dependent variables